The Impact of Web Browser Reader Views on Reading Speed and User Experience - Li, Qisheng; Morris, Meredith Ringel; Fourney, Adam; Larson, Kevin; Reinecke, Katherina (CHI 2019, 2019)
As reading increasingly shifts from paper to online media, many web browsers now provide a “Reader View,” which modifies web page layout and design for better readability. However, research has yet to establish whether Reader Views are effective in improving readability and how they might change the user experience. We characterize how Mozilla Firefox’s Reader View significantly reduces the visual complexity of websites by excluding menus, images, and content. We then conducted an online study with 391 participants (including 42 who self-reported having been diagnosed with dyslexia), showing that compared to standard websites the Reader View increased reading speed by 5% for readers on average, and significantly improved perceived readability and visual appeal. We suggest guidelines for the design of websites and browsers that better support people with varying reading skills.